2021
DOI: 10.3390/pr9101705
|View full text |Cite
|
Sign up to set email alerts
|

Internal Flow and Cavitation Analysis of Scroll Oil Pump by CFD Method

Abstract: In this study, a three-dimensional model with actual clearances was established for a scroll oil pump, and the internal flow was simulated by the CFD method. The internal flows at different rotation angles were studied, and the cavitation and pressure pulsation in the scroll pump under different working conditions were analyzed. The results show that the flow in the two working chambers of the scroll pump is asymmetric due to its structural characteristics and motion mode. The high-pressure pulsation occurs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Based on the results of the experimental simulation, they analyzed and proposed a new model that is suitable for laminar, turbulent, and cavitation flow. Tian et al [19] established a three-dimensional model of a scroll oil pump with actual clearance and found that the flow in the two working chambers was asymmetric. The author effectively improved pressure pulsation by increasing the axial clearance and reducing the rotational speed and proposed a method to reduce pressure pulsation by shortening the vortex profile.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the experimental simulation, they analyzed and proposed a new model that is suitable for laminar, turbulent, and cavitation flow. Tian et al [19] established a three-dimensional model of a scroll oil pump with actual clearance and found that the flow in the two working chambers was asymmetric. The author effectively improved pressure pulsation by increasing the axial clearance and reducing the rotational speed and proposed a method to reduce pressure pulsation by shortening the vortex profile.…”
Section: Introductionmentioning
confidence: 99%